Continuous wavelet transform analysis of projected fringe patterns - Dursun, A; Özder, S; Ecevit, FN (Iop Publishing Ltd, 2004)
3D profile measurement of an object is studied experimentally by using a standard fringe projection technique consisting of a CCD camera and a digital projector. The height profile of the object is calculated through the phase change distribution of the projected fringes from the phase and phase gradient of the wavelet transform. Experimental results for the Fourier transform profilometry algorithm are compared with the results of wavelet analysis.
Keywords: wavelet transform; fringe projection; 3D profile determination